2017
DOI: 10.1002/ccd.26883
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in peripheral arterial interventions: Observations from the blue cross blue shield of Michigan cardiovascular consortium (BMC2 PVI)

Abstract: There is a significant increase in patients presenting with CLI. Renal artery intervention rates are decreasing while femoral-popliteal interventions are increasing. Additionally, balloon angioplasty and cutting/scoring balloon usage is increasing. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Lower GFR, hypertension, diabetes, prior heart failure, anemia, and CLI were all independently associated with AKI. Similarly, Grossman et al using data from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium, 26 and Prasad et al 1 using clinical administrative data from the National Inpatient Sample, demonstrated a strong association between CLI and risk of AKI. These studies have further mirrored the coronary revascularization literature in that the occurrence of AKI following endovascular therapy is significantly associated with the need for renal replacement therapy and mortality.…”
Section: Discussionmentioning
confidence: 89%
“…Lower GFR, hypertension, diabetes, prior heart failure, anemia, and CLI were all independently associated with AKI. Similarly, Grossman et al using data from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium, 26 and Prasad et al 1 using clinical administrative data from the National Inpatient Sample, demonstrated a strong association between CLI and risk of AKI. These studies have further mirrored the coronary revascularization literature in that the occurrence of AKI following endovascular therapy is significantly associated with the need for renal replacement therapy and mortality.…”
Section: Discussionmentioning
confidence: 89%
“…Despite a lack of RCT data and comparative studies, particularly in Ao‐I vessels, specialty balloon usage has dramatically increased over time in lower extremity EVT. In the Blue Cross Blue Shield of Michigan Cardiovascular Consortium PVI Registry of 44,650 prospectively enrolled patients, specialty balloon (namely cutting balloon) utilization increased from 1.8% in 2006 to 15.1% in 2013 ( p trend < .001) 18 . Available outcomes data are observational and focus on immediate technical success and patency.…”
Section: Devicesmentioning
confidence: 99%
“…53 In a study of 44,650 PVIs performed in 43 hospitals from 2006 to 2013, a significant temporal trend was observed for PVI indications in treating CLI. 54 In 2006, 24.1% of the 1,677 PVIs were performed for CLI while 47.5% of the 9,185 PVIs were performed for CLI in 2013. The largest increase in PVI performed was for femoropopliteal disease, with no significant trend in aortoiliac or below-the-knee pathology.…”
Section: Outcomes and Mortalitymentioning
confidence: 99%